PENELUSURAN MIKROORGANISME PENGHASIL ANTIBIOTIKA DARI LIMBAH AIR DANGKE KABUPATEN ENREKANG SULAWESI SELATAN - Fitriana, Fitriana; Jurianti, Jurianti (Fakultas Farmasi UMI, 2013)
Has been studied antibiotic-producing microbial isolation from waste water districs dangke enrekang. Preliminary studies carried out using the method of casting on medium Nutrient Agar (NA) and Potato Dextrosa Agar (PDA) with dilutions of 10-1 to 10-5. The results of four isolates of microbes are active in NA medium and four isolatesPDA medium, and then observed in macroscopic and microscopic. Furthermore, bacterial and fungal isolates was purified by the method of quadrants on each medim Nurien Agar (NA) and Potato Dextrosa Agar (PDA). To produce antibiotis from microbial fermentation performed using Yeast Maltose Broth medium (MYB). The results of testing the activity of an antibiotic fermentation with agar diffusion method. The results showed that the bacterial isolates I and II Salmonella typhi and is active againts Candida albicans. Bacterial isolates I, II, III, and IV, were active againts Staphylococcus epidermis, Streptococcus mutans, Pseudomonas aeruginosa, Vibrio sp, Escherichia coli, Bacillus subtilis and Staphylococcus aureus. I fungal isolates active against Salmonella typhi. II and IV of fungal isolates active against Pseudomonas aeruginosa. IV fungal isolates active against Vibriosp, Escherichiacoli and Stapylococcusaureus.Key word : Studied Antibiotic-Producing, Waste Water, Dangke, Enrekang